LMD-09. Outcomes and symptom benefit from palliative radiotherapy for leptomeningeal disease in breast cancer patients. (9th August 2021) - Takayesu, Jamie; Sapir, Eli; Xie, Jiaheng; Sun, Yilun; Morikawa, Aki; Junck, Larry; Leung, Denise; Umemura, Yoshie; Heth, Jason; Al-Holou, Wajd; Wahl, Daniel; Lawrence, Theodore; et al.
Abstract: Objective: The benefit of radiotherapy (RT) in patients with leptomeningeal disease (LMD) is poorly characterized. This study assessed the overall survival (OS) and clinical improvement of a largely symptomatic cohort of breast cancer patients with LMD, to identify patient subsets most likely to benefit from palliative RT. Methods: Patients with breast cancer-related classic radiographic LMD (36% cytology-confirmed) were treated with palliative whole brain and/or partial spine RT between 2000–2020 at a single academic institution in this retrospective analysis. OS was calculated from date of LMD diagnosis using the Kaplan-Meier method. A multivariate logistic regression model incorporating ER/PR status, HER2 status, ECOG and steroid use was developed to identify factors associated with symptom benefit, which was ascertained retrospectively by chart review. Results: Among 64 patients, the radiographic distribution of LMD was in the brain (58%), spine (22%), or both (20%). A total of 63% had brain metastases, and 57% of patients had ER+ and/or PR+, 22% HER2+, and 38% triple-negative disease. Of the symptomatic patients (94%), primary symptom domains included cranial nerve deficits (34%), sensory/motor deficits from intracranial disease (25%) or spinal disease (27%), and headaches/nausea (14%), with 42% of patients reporting >1 symptom domain. Two-thirds of patients were on steroids prior to RT, and 13% of patients received intrathecal therapy. OS was 3.75 months. Following a median dose of 30Gy in 10 fractions, 59% of symptomatic patients experienced symptom improvement, with similar improvement rate across domains (12%, 15%, 19%, 14%, respectively); 21% of patients had improvement in >1 symptom domain. Hormone receptor positivity was independently associated with symptom improvement following RT (OR 3.5, 95% CI 1.2–11, p=0.029). Conclusions: In this poor-prognosis cohort of breast cancer patients with LMD, palliative RT yielded symptomatic improvement, and may be particularly beneficial among better-prognosis patients with hormone receptor-positive disease.